How much is the crime prevention programme for fraud worth? On the cost benefit analysis in the case of police with unsolved cases remaining - Lee, Youngsub (International journal of law, crime and justice, 2025)
This paper attempts to estimate the monetary value of preventive policing programmes that are being adopted by police forces around the world in response to growing concerns about economic crime. To do this, we reviewed existing studies on the cost of crime and cost-benefit analysis, set the standard for calculating the economic indicators using highly reliable data, and derived two indicators to measure the value of preventive policing against economic crime: the reduction in direct financial loss and the conditional reduction in criminal justice costs from reduced police officer workload. As a policing case to apply the indicators, we selected the National Counter Scam Centre's (NCSC) technology-based prevention and advice policy in the Korean police. By comparing two sets of data, we found that the victimisation rate of citizens who benefited from the policy was 1 %, which is 2.35 % lower than the victimisation rate of the general population of 3.35 %. Based on this, it is estimated that if 1239 (December 2023 average) preventative counselling sessions were provided every day for one year (249 working days), a total of around £101.4 million in direct harm would be prevented. However, in the case of criminal justice cost savings, we found that the remaining unsolved case problems in the target society would require police officers to work at full capacity, even with the preventive policing programme, which leads to no change in workload-based cost savings. As a result, this study found that the benefits of preventive policing are 58 times greater than the costs, while presenting new standards in criminal justice cost saving estimation, the issue of unsolved cases when estimating cost savings from workload changes in policing. However, the short timeframe of this study's methods (pre- and post-intervention) has the limitation in terms of its evidential robustness.